2018
DOI: 10.1038/s41598-018-29232-w
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of vitamin D synthesis in insects exposed to UVb light

Abstract: Vertebrates obtain the prohormone vitamin D primarily by endogenous cutaneous synthesis under ultraviolet b (UVb) exposure. To date, endogenous synthesis of vitamin D in insects has never been investigated. In an initial experiment, we exposed four insect species which differ in ecology and morphology (migratory locusts, house crickets, yellow mealworms and black soldier fly larvae (BSFL)) to a low irradiance UVb source. In a second experiment we exposed these species to a higher UV irradiance, and in a third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…These are considered a relatively sustainable source of animal protein and are perceived as highly nutritious (van Huis & Oonincx, ). Most insects are rich sources of protein, minerals, and certain vitamins, although great variation exists between species and life stages, and due to production conditions (Finke & Oonincx, ; Oonincx et al ., ). Additionally, most insect species contain large amounts of fat.…”
Section: Introductionmentioning
confidence: 97%
“…These are considered a relatively sustainable source of animal protein and are perceived as highly nutritious (van Huis & Oonincx, ). Most insects are rich sources of protein, minerals, and certain vitamins, although great variation exists between species and life stages, and due to production conditions (Finke & Oonincx, ; Oonincx et al ., ). Additionally, most insect species contain large amounts of fat.…”
Section: Introductionmentioning
confidence: 97%
“…UV radiation is the most important external cause of melanogenesis (Glady et al, 2018;Mishima and Tanay, 1968). Current studies have found that UV light can promote melanogenesis through epigenetic modifications (Zhang et al, 2019), DNA damage repair (Kemp et al, 2019;Oonincx et al, 2018), signal transduction (Hu et al, 2019), and the alteration of the MC microenvironment (Glady et al, 2018;Pei et al, 2018). It is well known that any biological behavior exerts positive and negative feedback to maintain homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Oonincx et al (2019) achieved optimal ratios by adding only 1-2% of flaxseed oil to the diet of house crickets, lesser mealworms, and black soldier flies. Oonincx et al (2018) also showed that insects can synthesize vitamin D de novo and that the amounts depend on UVb irradiance and exposure duration.…”
Section: Nutrition and Healthmentioning
confidence: 96%